Fiscal operations and its effects on economic growth and stability in Nigeria, 1980-2015 - Idris, Miftahu (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2018)
This study investigates the impact of fiscal operations towards ensuring sustainable growth in Nigeria. In doing so, it examines, among other things, the trend and structure of fiscal operations in Nigeria, the impacts of government expenditure and taxation (as fiscal components) on economic growth and stability, the response of debt and openness of the economy on GDP and CPI, evaluates the short-run and long-run dynamics and possible interdependence among the variables, measures the imoact of policy shocks on examined variables in the model, and incorporate a dummy variable in both models to measure the effects of administrative changes from the military system to a democratic system in Nigeria.